Unexpected Revolution: The Role of Social Media in Ukraine's Euromaidan Uprising. Issue 1 (June 2014) - Bohdanova, Tetyana
As people become increasingly connected online, more and more social and political movements sparked by new information and communication technologies emerge around the world. While these technologies enable quick mobilisation of a large number of participants for a particular cause, not all social media-empowered initiatives are equally successful in becoming sustainable and achieving their goals. This paper examines the role of social media in Ukraine's recent Euromaidan uprising. In particular, it looks at the strategic ways in which activists have used social media for protest mobilisation, internal and external communication and organising. It concludes by discussing the limits to the use of technology in Euromaidan as well as the particular challenges of online organising.